(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
International trades between countries and acrosscontinents have existed for centuries including previous civilizations.Traditionally international trade consisted of traded goods like textile, fooditems, spices, precious metals, precious stones, and objects of art and variousitems across the borders. Everybody has heard of the silk route as well asamber road and other famous routes that existed and the ports and settlementsthat flourished due to the trade, which was carried on through land route aswell as sea routes.